Changes in objectively measured physical activity after a multidisciplinary lifestyle intervention in children with abdominal obesity: a randomized control trial - Lydia Morell-Azanza; Ana Ojeda-Rodríguez; Amaia Ochotorena-Elicegui; Nerea Martín-Calvo; María Chueca; Amelia Marti; Cristina Azcona-San Julian (BMC, 2019)
Abstract Background Physical activity (PA) is associated with changes in body composition that affect insulin sensitivity and leptin levels. Few studies have assessed the effect of lifestyle interventions on changes in objectively measured PA levels in obese children. To evaluate the effects of a multidisciplinary lifestyle intervention on anthropometric indices, biochemical parameters and accelerometer measured PA in abdominal obese children. Methods A randomized control trial was performed in 106 children and adolescents with abdominal obesity. Participants were randomly assigned to usual or intensive care group for 8-week. PA was measured by accelerometry over four days including, at least, two weekdays in all participants. Both groups were encouraged to accumulate an extra time of 200 min per week in their PA. Results At baseline, 75% of subjects do not fulfill the WHO recommendation of being more than 60 min/day on moderate-to-vigorous PA (MVPA). The intensive care group achieved a significant reduction in anthropometric indexes compared to the usual care but no significant change was found in biochemical or PA parameters. Both groups achieved a significant reduction in light PA. Interestingly, intensive care participants significantly increased MVPA in 5.5 min/day. Moreover, an inverse association between changes in MVPA and leptin levels was found. Conclusion The two lifestyle intervention reduced anthropometric indexes and lowered light PA in abdominal obese children. No significant differences were observed between intensive care and usual care in regard to PA. Intensive care participants significantly increase physical activity (MVPA) and, changes in MVPA were inversely associated with changes in leptin levels after the intervention. Trial registration ClinicalTrials.gov, Identifier: NCT03147261. Registered 10 May 2017. Retrospectively registered.